The Effect of Focus and Attention and Its Correlation with the Accuracy of Spike Performance with the Rotation and Deception in Volleyball - Majid Hameed Merzah (Journal of Global Pharma Technology, 2018)
The current study aimed to identify the relationship of statistical research to the effect of concentration and attention and their relation to the accuracy of the performance of the spike and rotation of the volleyball of the sample of the research, which was subjected to the test of the impact of concentration and attention to volleyball and the skill test dealt with the study. The researchers used the experimental method to suit the nature of the research, where the study was conducted on a sample of students of the second stage in the Faculty of Physical Education / Karbala University for the academic year 2017 (2018) and represent the age group (20 - 22) years, the number of (60) students, (80%) of the original research community were selected by random method. The researcher used the following statistical means (Percentage, mean, standard deviation, and correlation coefficient - Pearson). The researchers concluded that the concentration and attention test showed a significant correlation in the spike test and the volleyball deception.Keywords: Focus and attention, He spike of rotation, The spike of deceit and volleyball.